A place to stand: Digital sociology and the Archimedean effect. (December 2017) - Possamai-Inesedy, Alphia; Nixon, Alan
With the advent of the internet, particularly Web 2.0, sociologists have been called to take up the challenges and the promises of the web. In the face of this, sociologists are caught up in debates and practices concerned with how to ethically approach and develop appropriate methods/methodologies for the field. While these are important endeavours, more robust debate needs to take place on the unintended consequences of the promises of the internet, as well as the power relations that are at play in what we term the 'digital social'. Employing the metaphor of the Archimedean screw and Archimedean point, this article argues that the space we now find ourselves in is unprecedented; it is one which simultaneously demands the empowerment of research and yet results in the stripping away of its foundation. The Archimedean effect demonstrates that the promises of the internet have not been fulfilled resulting in the evolution and de-evolution of the digital social framed by the reinforcement of existing power relations. Yet, rather than viewing this as a time of crisis, we should see it as a defining moment for our discipline, one where the demands of public sociology need to be adopted broadly.